From the kaleidoscope of the tribal life to ethnography - Sirimarco, Mariana; Daich, Deborah (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2021)
As researchers and professors, we have been lately perceiving some difficulties in the construction of anthropological research -mostly in students and recent graduates. We are specifically referring to a certain degree of deterioration in some epistemological and basic guidelines of our discipline -the scope of the research and the anthropological question of a text. This paper explores the formulation and the challenges of these analytic tools, taking into account methodological, epistemological, moral and political perspectives. It does not pretend to crystallize definitions nor offer textbook techniques, but simply to outline some reflections, with ultimate pedagogical aims.